Cassava wastewater as a substrate for the simultaneous production of rhamnolipids and polyhydroxyalkanoates by Pseudomonas aeruginosa - Costa, Siddhartha G. V. A. O. [UNESP]; Lepine, Francois; Milot, Sylvain; Deziel, Eric; Nitschke, Marcia; Contiero, Jonas [UNESP] (Springer Heidelberg, 2009)
Glycerol, cassava wastewater (CW), waste cooking oil and CW with waste frying oils were evaluated as alternative low-cost carbon substrates for the production of rhamnolipids and polyhydroxyalkanoates (PHAs) by various Pseudomonas aeruginosa strains. The polymers and surfactants produced were characterized by gas chromatography-mass spectrophotometry (MS) and by high-performance liquid chromatography-MS, and their composition was found to vary with the carbon source and the strain used in the fermentation. The best overall production of rhamnolipids and PHAs was obtained with CW with frying oil as the carbon source, with PHA production corresponding to 39% of the cell dry weight and rhamnolipid production being 660 mg l(-1). Under these conditions, the surface tension of the culture decreased to 30 mN m(-1), and the critical micelle concentration was 26.5 mg l(-1). It would appear that CW with frying oil has the highest potential as an alternative substrate, and its use may contribute to a reduction in the overall environmental impact generated by discarding such residues.
Keywords: Cassava wastewater; Glycerol; Polyhydroxyalkanoates; Pseudomonas aeruginosa; Rhamnolipids; Waste cooking oil